دراسة مرجعية إلداء الرصف الخرساني بالمطارات بمناطق االجواء الحارة في ليبيا (Comprehensive Journal of Science, 2025)
Libya is characterized by a relatively moderate climate in the north and a desert climate(hot and dry) in the south, where the desert climate areas are characterized by high temperatures andlow rainfall rates in addition to the large change in temperatures between night and day, and due tothe presence of many airports in these southern regions. It has aircraft parking areas andmaintenance areas. Therefore, many problems appeared in the concrete paving at the constructionjoints in these areas, resulting in poor paving performance. This study aims to identify the causesand mechanisms of damage to concrete paving in airports located in hot, dry areas in Libya and tosuggest treatment methods. And to know concrete paving and construction joints.This study included a field and reference study of airports located in hot climate areas, namelyGhadames, Sebha, airports, to identify all concrete pavements, construction joints between concretepavements and asphalt shoulders, and the transition zone between concrete pavements and asphaltpavements, and to identify the prevailing and similar damages to concrete pavements at theseairports.By analyzing the causes of damage, it became clear that most of them in concrete pavement aredirectly or indirectly related to the movement of concrete slabs. It was found that the damages weresimilar, namely the widening of the gaps between the concrete pavement and the asphalt shoulders,their filling with sand, and the elevation of the asphalt pavement above the level of the concretepavement surface. The expansion joints widened by a distance of up to 5 cm and were filled withsand, as at Sebha Airport, and some contraction joints widened by a distance of up to 10 cm andwere filled with sand, as a result of the thermal expansion of the concrete and the rise intemperatures. It became clear that the gap between the concrete and asphalt pavement at the end ofthe buried concrete slab widens during the shrinkage movement and is penetrated by sand. Whenthe concrete pavement expands, the asphalt pavement rises upwards as a result of the concretepavement pushing on it. The asphalt pavement collapses. Treatment methods were suggested usinga camera to prevent movement transfer between the concrete and asphalt pavement, as well aspaving a strip 1.5 to 2 meters wide with aggregate only, adjacent to the concrete pavement. Wideexpansion joints are treated by removing the entire slab and re-pouring it.One of the conclusions of this study is that the failure of the designs did not take into account theenvironmental conditions at Ghadames Airport, such as the large change in temperatures, whichcaused excessive expansion and contraction, and thus an increase in the value of the coefficient ofexpansion of the concrete. This repeated thermal movement caused the expansion of the joints.When constructing concrete pavements in hot areas, it was recommended that the distance betweenexpansion joints should not exceed 30 metres, that the reinforcement mesh should be continuous